ANALISIS PENDAPATAN DAN PEMASARAN USAHATANI BAWANG MERAH DI DESA PURWOREJO KECAMATAN NGANTANG KABUPATEN MALANG - Syamsul Arifin; Sri Hindarti; Farida Syakir (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
This study aims to 1) Knowing the efficiency of farming onions, 2) Know the margins and distribution margins in onion farming and 3) Analyze the efficiency of onion marketing in Purworejo Village, Ngantang District, Malang Regency. This research is a combination of descriptive and quantitative methods. Sampling using simple random sampling method. With a sample of 40 shallots farmers from 396 populations on the basis of the sampling method according to (Surachmat, 1998) researchers determined 10% of the population of farmers in Purworejo Village. Whereas to determine respondents marketing institutions use the snowball sampling method. The results showed the average cost incurred in one planting season was Rp 9,644,958 known to the average production of farmers as much as 3,609 kg with an average price of Rp 9,780 / kg. So there is an income of Rp 35,293,575 and an average income of farmers of Rp 25,648,616 so that an average R / C Ratio of 3.59 is obtained, which means the farm is feasible to be cultivated where the R / C ratio is greater than 1. Marketing channels there are two channels (I) farmers to middlemen from middlemen are sold again to large traders and then to retailers until the end consumers, (II) farmers to wholesalers, retailers then to end consumers. The most efficient marketing channel is the marketing channel II with a smaller margin of IDR 12,500 compared to marketing channel I with a margin of IDR 13,500. Marketing channel II is more efficient because the marketing chain is shorter than marketing channel I.